2023
DOI: 10.7554/elife.81070
|View full text |Cite
|
Sign up to set email alerts
|

The forgotten people: Hepatitis B virus (HBV) infection as a priority for the inclusion health agenda

Abstract: Hepatitis B virus (HBV) infection represents a significant global health threat, accounting for 300 million chronic infections and up to 1 million deaths each year. HBV disproportionately affects people who are under-served by health systems due to social exclusion, and can further amplify inequities through its impact on physical and mental health, relationship with stigma and discrimination, and economic costs. The ‘inclusion health’ agenda focuses on excluded and vulnerable populations, who often experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 117 publications
2
19
0
Order By: Relevance
“…These findings are not surprising, as antenatal care attendance and delivery in healthcare facility provides opportunities for educating mothers on the benefits of vaccination and other vital maternal and child health services [31, 32]. Taken all together, our findings are in agreement with others who have suggested that HBV infection is fundamentally a disease of poverty [33, 34]; thus, HBV control efforts should aim to address socioeconomic inequities to achieve elimination targets [9, 33, 34].…”
Section: Discussionsupporting
confidence: 91%
“…These findings are not surprising, as antenatal care attendance and delivery in healthcare facility provides opportunities for educating mothers on the benefits of vaccination and other vital maternal and child health services [31, 32]. Taken all together, our findings are in agreement with others who have suggested that HBV infection is fundamentally a disease of poverty [33, 34]; thus, HBV control efforts should aim to address socioeconomic inequities to achieve elimination targets [9, 33, 34].…”
Section: Discussionsupporting
confidence: 91%
“…The global pooled HIV prevalence ratio over the last decade was higher for international migrant people, compared with their native counterparts (Prevalence ratio [PR] = 1.70) and was also significantly elevated for refugees (PR = 2.37). Those migrating from the African continent had the highest HIV prevalence ratio (PR = 3.81); those from the Middle East, western Europe and eastern Europe had a lower prevalence ratio compared with the host population (0.56, 0.67 and 0.64, respectively) [28].…”
Section: Resultsmentioning
confidence: 96%
“…Incidence and prevalence of other STIs, such as hepatitis B and C and syphilis, have risen over the last decade among MIDP compared to native counterparts [28,29 ▪ ], with a reported increase among those from sub-Saharan Africa and Northeast and Southeast Asia [30]. Syphilis prevalence was elevated among a sample of migrant people in transit through Mexico (4.5%) compared to local populations (0.92%), and among Venezuelan immigrant and refugee populations in Colombia (5.1%), compared to Colombian adult population (1.3%) [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…Engagement in research has not historically been equitable or representative in the field of HBV. 7 A larger study cited by Khalili et al 1 that evaluated the HBV cascade in a national claims database and also found no difference in treatment uptake by race may be more generalizable but should also be viewed with caution, since it did not include a broader sample of publicly insured individuals. 5 A critical aspect of examining the HBV care cascade through the lens of equity is acknowledging the role that health systems play in perpetuating inequities.…”
Section: + Related Articlementioning
confidence: 95%
“…There may have been implicit exclusions from this study due to socioeconomic, cultural, and language barriers, as well as differing levels of trust in health care and research institutions. Engagement in research has not historically been equitable or representative in the field of HBV . A larger study cited by Khalili et al that evaluated the HBV cascade in a national claims database and also found no difference in treatment uptake by race may be more generalizable but should also be viewed with caution, since it did not include a broader sample of publicly insured individuals …”
mentioning
confidence: 99%